P259 Central Nervous System Tuberculosis: Diagnostic Difficulties. (12th November 2015) - Macpherson, L; Cuthbert, R; Potter, J; White, V; Jayasera, N; Kunst, H
Abstract : Introduction: Central nervous system (CNS) tuberculosis (TB) is difficult to diagnose. There is often a delay in diagnosis and a lack of robust diagnostic criteria. Methods: We conducted a retrospective study of all patients treated at our institution for CNS TB from 2009–2014 excluding those with HIV co-infection. Data including demographics, symptoms, microbiological and radiological features was recorded. Results: 55 cases of CNS TB were identified. The mean age was 36 (4 months – 81 years). Most patients were from the Indian Subcontinent (70.9%), 10.8% were from South East Asia, 1.8% from Africa, 10.9% were UK born and 5.5% were unknown. Symptoms and signs at presentation included headache (67.3%), fever (49%), confusion (34.5%), focal neurological deficit (27.3%), weight loss (27.3%), night sweats (23.6%), altered GCS (23.6%) and seizures (20%). 29% of patients also had pulmonary TB, 11% had TB lymphadenopathy and 11% had miliary TB. 89% of patients had a CT head, of which 42.8% were reported normal, 28.5% reported tuberculomas, 14.2% hydrocephalus and 20.4% exhibited other abnormalities. 87% had an MRI head, of which 10% were normal, 39.6% reported tuberculomas, 33% meningeal enhancement, 6% hydrocephalus, and 23% demonstrated other abnormalities. Lumbar puncture (LP) was performed in 73% of cases, and CSF protein was elevated in 73% of these. The WCC was elevated in 60% with 63% having a predominant lymphocytosis. CSF Glucose was documented in 80% of cases and levels were low (<2.5 mmol/L) in 47%. TB PCR was performed on 15 samples (38%), 2 (13%) were positive. Five CSF samples were not sent for AFB or culture. No samples were smear positive, 26% of CSF samples were culture positive; one was Isoniazid resistant. 7 patients died (one death attributed to TB chemotherapy), 3 became fully dependent for all activities of daily living and 6 patients had significant cognitive or neurological deficit. Conclusions: CNS TB causes significant morbidity and mortality. CSF examination should always be performed if feasible. Imaging by MRI should be considered in all patients with suspected TB meningitis in view of the much higher diagnostic yield compared to CT.